Authority to consent to the use of force in contemporary international law: the Crimean and Yemeni conflicts. (2nd January 2019) - Wong, Isabella
ABSTRACT: This article analyses the legal framework by which consent may justify a prohibited use of force in the context of two internal conflicts: Russia's intervention in Crimea in 2014 and the Saudi-led intervention in Yemen since 2015. First, it contends that the valid consent of a legitimate government may constitute a legal justification for a foreign military intervention where it does not interfere with the political independence of the inviting government, or constitutes a 'counter-intervention'. Secondly, it finds an ostensible absence of authority to consent in both the Crimean and Yemeni conflicts, which implies that the interventions amounted to a prohibited use of force. Thirdly, it discerns from the extensive condemnation of the Russian intervention and the widespread acquiescence to the Saudi-led intervention in state practice and the academic literature a paradoxical interpretation of the legality of the interventions.